Antimicrobial Effect of Asiatic Acid Against Clostridium difficile Is Associated With Disruption of Membrane Permeability - Harnvoravongchai, Phurt; Chankhamhaengdecha, Surang; Ounjai, Puey; Singhakaew, Sombat; Boonthaworn, Kanpong; Janvilisri, Tavan (Frontiers in Microbiology, 2018)
Antibiotic resistance is a major concern in Clostridium difficile, the causative agent of antibiotic-associated diarrhea. Reduced susceptibility to first- and second-line agents is widespread, therefore various attempts have been made to seek alternative preventive and therapeutic strategies against this pathogen. In this work, the antimicrobial properties of asiatic acid were evaluated against C. difficile. Asiatic acid displayed substantial inhibitory effects on 19 C. difficile isolates collected from different sources with minimal inhibitory concentrations ranging from 10 to 20 μg/ml. Time kill analysis and minimal bactericidal concentration revealed potential bactericidal activity of this compound. Asiatic acid induced membrane damages and alterations in morphological ultrastructure in C. difficile, thereby causing the leakage of intracellular substances. Moreover, asiatic acid also displayed an inhibitory effect on cell motility, but did not interfere with biofilm formation and spore germination. Analysis of drug combination showed no synergistic effect between asiatic acid and vancomycin/metronidazole. Altogether, asiatic acid exhibited strong antimicrobial activity against vegetative cells and could serve as an alternative resource for tackling C. difficile.